Strategic Market Reversal Mechanisms of Latecomer Battery Firms: A Comparative Analysis of CATL vs. Panasonic/LG Chem (aSSIST Business Review, 2026)
This study analyzes how a latecomer firm in the global battery industry succeeded in overtaking established leaders, revealing the structural dynamics of strategic execution mechanisms. China’s CATL surpassed incumbents such as Panasonic and LG Chem to become the global market leader in a relatively short time. This paper systematically examines the strategic design behind CATL’s rise using the SER-M (Subject, Environment, Resource, Mechanism) framework and the WSM (Weight and Sequence Model).The analysis identifies three critical success factors: agile Capex investment, customer-tailored manufacturing flexibility, and precise alignment with government policy timing. Additionally, the study reviews the ESG-based differentiation strategy of Umicore as a supplementary case, illustrating that non-technological execution mechanisms can also provide sustainable competitive advantages. The findings suggest that even latecomer firms can become market leaders if they combine executional design, strategic resource deployment, and environmental sensitivity.
Keywords: Latecomer firms; strategic execution; SER-M; WSM; Capex; ESG; execution mechanism